Diagnostic Difficulties in Pathological Laboratories in Developing Countries: A Case Report of Differentiated Squamous Cell Carcinoma in a Young Togolese Woman - Tchin Darré (Case Reports in Pathology, 2016)
We report a case of poorly differentiated squamous cell carcinoma of the vulva induced by human papillomavirus in a 23-year-old woman, in whom we experienced diagnostic difficulties.